Spray drying of the buriti pulp at different maltodextrin concentrations and temperature - Gomes, Wolia Costa; Figueirêdo, Rossana Maria Feitosa; Queiroz, Alexandre José de Melo; Rodrigues, Alyson da Luz Pereira; Cruz, Glauber; Mendes Villis, Paulo Cesar (Ciência e Natura, 2018)
In this work, the formulations prepared with buriti pulp and different maltodextrin concentrations (5, 10 and 15%) were dried in spray dryer and the chemical, physical and physical-chemical characteristics of the formulations and powder samples were evaluated. In this drying process two kinds of powder samples were collected: one into drying chamber and another in the cyclone. Using a factorial experimental planning, the experiments were conducted, in order to assess the moisture and ash contents, total acidity and density of both samples. The formulations dried in the spray dryer presented be feasible for the production of buriti pulp powder; however, powder samples collected into drying chamber and cyclone were different. Among the parameters analysed, it was found that only for density the samples collected into drying chamber, that the first-order empirical model obtained was statistically significant and predictive.